The Relationship of the −5, −8, and −24 Variant Alleles in African Americans to Triosephosphate Isomerase (TPI) Enzyme Activity and to TPI Deficiency - Schneider, Arthur; Forman, Linda; Westwood, Beryl; Yim, Catherine; Lin, James; Singh, Satinder; Beutler, Ernest (Blood, 1998)
In 424 African-American and 75 white subjects, we found that the −5 (TPI 592 A→G), −8 (TPI 589 G→A), and −24 (TPI 573 T→G) variants in the triosephosphate isomerase (TPI) gene occurred frequently (41.0%) in the African-American subjects but did not occur in the whites. These data suggest that this set of polymorphisms may turn out to be one of the higher-incidence molecular markers of African lineage, a surprising finding because others had reported that these nucleotide substitutions were restricted to a small subset of African Americans who had been characterized as TPI-deficiency heterozygotes. Additionally, we investigated the relationship of these variants to TPI-enzyme activity. Although the variant substitutions (occurring in three haplotypes: −5 alone, −5 −8, and −5 −8 −24) were associated with moderate reduction in enzyme activity, severe-deficiency heterozygotes could not be identified with certainty, and none of the haplotypes were restricted to subjects with marked reduction of enzyme activity. Three subjects were homozygous for the −5 −8 haplotype, a finding inconsistent with the putative role of this haplotype as the cause of a null variant incompatible with life in homozygotes. Despite these findings, the possibility remains that the −5 −8 or −5 −8 −24 haplotypes may in some instances contribute to compound heterozygosity and clinical TPI deficiency. © 1998 by The American Society of Hematology.